The relationships between corporate meeting planner's personality traits and their choices of meeting places - M. Ariffin, Ahmad Azmi; Ishak, Nor Khomar (Universiti Utara Malaysia, 2007)
This study is to determine the influence of personality on the novelty preference for corporate meeting destination choice. The Big-Five model of personality which consists of five traits namely openness, conscientiousness, extraversion,agreeableness, and neuroticism was employed to operationalise the personality construct. A total of 75 corporate meeting planners drawn from public listed service organisations were involved. The main method of data collection was questionnaire survey and multiple regression analysis was employed as the main statistical analysis. The results revealed that only openness (positively) and agreeableness (negatively) contributed significantly to the prediction of novelty preference for corporate meeting destination choice. This study, which also seeks to determine the relationships between some demographical variables and novelty preference, found that demographical information is not a good predictor of meeting destination choice. The main implication of this study is pertaining to the segmentation and targeting of the corporate meeting market. This study also helps in bridging the gap between tourism marketing and organisational research.